THE SPIRIT OF TECHNOLOGY IN E-GOVERNMENT: DESIGNING DEMOCRACY CAPABILITIES FOR ONLINE CITIZEN-GOVERNMENT INTERACTION - Guth, Kristen; Brabham, Daren (AoIR Selected Papers of Internet Research, 2015)
This paper aims to better understand the various democratic ideals manifested in designs of online crowdsourcing tools that are contracted by government entities. It seeks to answer questions about crowdsourced tools that are developed to serve a democratic purpose, including: (1) how are designers’ intentions incorporated? (2) what are the imagined user groups? and (3) what are the expected outcomes? The startup and technology vendors that contract with North American government bodies provide a particular context in which democratic freedoms are valued. The sample for this study consists of firms that have contracts for crowdsourced tools with Canadian or American government bodies. Questions were addressed through interviews with the founders or programmers of these technology firms to learn about the design of their products. To advance knowledge across disciplinary boundaries, we review literature on design from science and technology studies, democratic values from political science, and stakeholder theory from management. This study reveals how these perspectives have implications for contracting practical, technical solutions for government.